2016
DOI: 10.1002/chem.201600445
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of β‐Silicon‐β3‐Amino Acids in the Antimicrobial Peptide Alamethicin Provides a 20‐Fold Increase in Membrane Permeabilization

Abstract: Incorporation of silicon-containing amino acids in peptides is known to endow the peptide with desirable properties such as improved proteolytic stability and increased lipophilicity. In the presented study, we demonstrate that incorporation of β-silicon-β3-amino acids into the antimicrobial peptide alamethicin provides the peptide with improved membrane permeabilizing properties. A robust synthetic procedure for the construction of β-silicon-β3-amino acids was developed and the amino acid analogues were incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…However, simulations at higher temperatures and under an electric field resulted in peptide insertion within 1 µs. Madsen et al [20] showed that incorporation of silicon-containing amino acids in Alm introduced a 20-fold increase in membrane permeability. Similarly, Das et al [21] discussed an effective strategy to improve antibacterial activity of peptaibols by capping the N-terminal with 1,2,3-triazole, and with hydrophobic substituents on C-4.…”
Section: Introductionmentioning
confidence: 99%
“…However, simulations at higher temperatures and under an electric field resulted in peptide insertion within 1 µs. Madsen et al [20] showed that incorporation of silicon-containing amino acids in Alm introduced a 20-fold increase in membrane permeability. Similarly, Das et al [21] discussed an effective strategy to improve antibacterial activity of peptaibols by capping the N-terminal with 1,2,3-triazole, and with hydrophobic substituents on C-4.…”
Section: Introductionmentioning
confidence: 99%
“…[24] The antimicrobial values (minimum inhibitory concentration, MIC) of synthetic alamethicin 1 and analogue 5 against Grampositive S. aureus and Gram-negative E. coli were determined ( Table 1). Interestingly, recent studies have documented that substitution of the native amino acids in alamethicin with -silicon-3-amino acids results in a 20-fold increase in membrane permeability, [25] and the incorporation of α,α-substituted disilylated amino acids modified the physicochemical properties of the alamethicin analogues. [2] The antimicrobial assay showed that the replacement of the C-terminal alcohol in 1 for the C-terminal carboxylic acid in 5 had no significant effect on the activity.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of studies of C ‐silylated carbohydrates are striking as C−Si bond formation has received considerable attention in other natural product classes, for example, peptide chemistry, and other areas of bio‐ and medicinal chemistry, examples of this are metalloprotease inhibitors [23] and pseudo‐peptides [24, 25] …”
Section: Methodsmentioning
confidence: 99%